Integrated Resource Allocation and Scheduling in Bidirectional Flow Shop with Multi-Machine and COS Constraints - LAU, Hoong Chuin (Institutional Knowledge at Singapore Management University, 2009)
An integer programming (IP) model is proposed for integrated resource allocation and operation scheduling for a multiple job-agents system. Each agent handles a specific job-list in a bidirectional flowshop. For the individual agent scheduling problem, a formulation is proposed in continuous time domain and compared with an IP formulation in discrete time domain. Of particular interest is the formulation of the machine utilization function-- both in continuous time and discrete time. Fast heuristic methods are proposed with the relaxation of the machine capacity. For the integrated resource allocation and scheduling problem, a linear programming relaxation approach is applied to solve the global resource allocation and a fast heuristic method is applied to solve each scheduling subproblem. The proposed solution is compared experimentally with that from the integer programming solver by CPLEX.